The effect of dietary antioxidants on the arginase activity and nitric oxide level of freshwater crayfish (Astacus leptodactylus, Esch. 1823) - Barim, Ozden; Erisir, Mine (KAFKAS UNIVERSITY, 2009)
The effects of dietary antioxidants (vitamin E (VE), vitamin C (VC), vitamin A (VA), astaxhantin (ASX), ?-carotene (?C)) on the arginase activity and nitric oxide (NO) level of the hepatopancreas, muscle, ovarian and gills of freshwater crayfish (Astacus leptodactylus) were investigated. In the investigation, 150 mg kg-1 VE, 200 mg kg-1 VC, 240 mg kg-1 VA, 200 mg kg-1 ASX and 200 mg kg-1 ?C were added to experimental diets. The study was carried out for 144 days. The arginase activity in the hepatopancreas were significantly higher in the VE, VC and VA diet groups in the comparison to control (P<0.001), but NO level was lower in all diet groups compared to the control (P<0.001). Arginase activity and NO level in the muscle were significantly higher in the some diets groups (arginase; VE, VA, ASX, ?C, NO; VC, ASX) according to control (P<0.001). The arginase activity and NO levels in the ovarian were significantly lower in the all diet groups in the comparison to control (P<0.001). However, no significant differences in the arginase activity and NO level in the gill were observed among diets. The arginase activity and NO level in the hepatopancreas, muscle and ovarian were changed by dietary supplement of the antioxidants.
Tatlısu istakozu (Astacus leptodactylus, Esch. 1823)'nun arginaz aktivitesi ve nitrik oksit seviyesi üzerine rasyon Antioksidanlarıın etkisi
Keywords: Antioxidants; Arginase; Astacus leptodactylus; Nitric oxide